Samuel Beckett and the Islamic World: Connecting the Dots Through Beckett’s Works and Reception - Dr Muhammad Saeed Nasir (University of Chitral Journal of Linguistics and Literature, 2021)
The distinguished position of Samuel Beckett is due to his assignation of religious ideas. A quick closer look however reveals that Beckett has been studied from a Western perspective which is either religious or critical. A few studies on Beckett are from an Eastern viewpoint but Muslims’ perspective still is missing. Keeping this research gap in mind, the current paper aims to determine the significant impact of the Islamic perspective on Beckett’s works and how his works are adapted in various Muslim contexts. For this purpose, the adaptations of Waiting for Godot are used for finding out the connection between Beckett and the Islamic world. The findings of the paper highlight not only the presence of Beckett in the Islamic world but also the work offers rich signs in need to be traced.